C18 Track TGHD Minipig – Assessing Resource Holding Potential Behaviour as part of a Battery for Phenotyping TGHD Minipigs. (17th September 2014) - Ott, S; Schramke, S; Schuldenzucker, V; Wirsig, M; Schubert, R; Frank, F; Marcegaglia, M; Hölzner, E; Reilmann, R
Abstract : Background: The TRACK tgHD minipig project aims to evaluate the phenotype of the Libechov tgHD minipig model. Established tests for assessing different domains of possible phenotype manifestation in minipigs are lacking. The test introduced here is thought to primarily target behavioural dysfunction. Aim: To assess the feasibility and tolerability of the application of the test in minipigs and explore the tgHD minipigs' performance compared with that of wildtype (wt) minipigs. Methods/techniques: Thirty-two minipigs – 18 wt and 14 tg (124 Q) – were tested at an age of 6–8 and 11–14 months. The animals were housed in six mixed groups (wt and tg). Tests were conducted in a narrow aisle divided in half by a door. During training, the minipigs learnt to enter the aisle from one side, wait at the door, leave the aisle on the other side and receive a highly favoured food treat here. During testing, two animals entered the aisle from either end. The door was then opened and the animals faced each other. A "win" was noted for reaching the opposite end of the aisle first, pushing the conspecific aside. All animals per group faced each other once. Number of wins per encounters were compared between wt and tg minipigs. Data were analysed using SPSS 22.0. Results/outcome: Aged 6–8 months, wt minipigs won 42.86% ± 17.62% of the encounters, and tg minipigs 56.67% ± 31.10% (n.s.). Aged 11–14 months, wt minipigs reached 44.61% ± 31.45% wins per encounters, and tg minipigs 53.29% ± 25.73 (n.s.). Conclusion: Capability to fight conspecifics to receive or defend resources, i.e. the resource holding potential (RHP), depends on physiological (e.g. age, weight, health status) and psychological factors. The results show that assessment of the RHP is feasible using the test applied in minipigs. So far genotype has not shown a significant effect when comparing wt and tgHD minipigs. However, we hypothesise the test may be sensitive to detect a phenotype the cohorts grow older.